The Use of Micro Retractor in Endoscopic Endonasal Posterior Pseudocapsule Resection of Pituitary Macroadenoma. Technical Note - Xie, Tao; Zhang, Xiaobiao; Qu, Chenghui; Li, Chen (Frontiers in Oncology, 2021)
Background: The endoscopic endonasal approach and extra-pseudocapsule resection may be the main progress in modern pituitary surgery. However, for pituitary macroadenomas, discerning the pseudocapsule in the posterior plane of the tumor may be difficult. When the anterior-inferior debulking is performed, the early subsidence of the thinning normal pituitary gland and enlarged diaphragm may obstruct the surgical dissection view. Method: We describe the technique of using a micro retractor for the endoscopic endonasal posterior pseudocapsule resection of pituitary macroadenomas. This micro retractor that was 2mm in width was placed at the 12 o’clock position on the nostrils, and the end was fixed in the flexible arms of the self-retaining retractor system. The head of the micro retractor elevated the herniated diaphragm sellae in order to continue the posterior pseudocapsule resection of the pituitary macroadenoma. Result: The technique was performed very easily and no complication was observed. Conclusion: The use of this micro retractor can increase the view of the posterior margin of the adenomas to facilitate the pseudocapsule dissection.